Iot Based Plants Disease Detection Using Convolution Neural Network (CNN) and Support Vector Machines (SVM) - M.Saravanan, M.Ramkumar*, M.Sharon Nisha, Rajesh.N, M.P. Thiruvenkatasuresh (International Journal of Advanced Science and Technology, 2020)
Every country’s economic is extremely reliant on agricultural efficiency. Thus in the field offarming, increasing the yield is very important and for increasing the yield, the detection of disease inthe early stage in plant is essential. In order to identify a plant disease the utilization of an automateddisease detection strategy is helpful in protecting the plants and in increasing the yield. In this paperwe proposed a method for detecting the disease in banana leaves using IoT devices with the help ofconvolution neural network and support vector machine and we suggested a method for automationby robotics in forming. In the proposed work an algorithm for picture segmentation is developed fordetection of leaf diseases in banana tree. Also, the convolution neural network is utilized to determinethe kinds of disease. From the experimental results it is absorbed that our proposed method givesmore accurate result than the existing methods